Enhancing social skills: Reliability and validity of the Indonesian version of SSIS-RS among physical education students - Mulyana, Fegie Rizkia; Suherman, Adang; Mahendra, Agus; Subarjah, Herman; Hidayat, Yusuf (Journal Sport Area, 2024)
Background Problems: Social skills development is increasingly important in education as it impacts students’ social interactions, good relationships, and academic success. However, in the digital age, changing social dynamics are driving educators and researchers to recognise the importance of valid and reliable tools to assess and develop social skills, including in primary, secondary, and tertiary schools. Research Objectives: This study aims to discuss the process of adapting an instrument to assess adolescent social skill in higher education, highlighting the key considerations and steps involved in its development. Methods: The research method used was quantitative research. The population in this study were 1st semester physical education students, the sampling technique was purposive sampling, and the sample size was 118, data were discussed with Pearson and Cronbach. The English version of the SSIS-RS was translated according to international guidelines into Indonesian. Content validity was verified by an expert panel and our instrument was then administered to the two sample physical education classes. SPSS version 27.0 (SPSS Inc, Chicago, IL) was used to perform all analyses in this study. Findings and Results: The results of the instrument validity test using Pearson correlation showed that 45 statement items were valid (r count > r table) of 46 statement items. It could be concluded that the Indonesian version of the SSIS-RS instrument had achieved adequate group validity. Cronbach alpha ranged from 0.888-0.893, indicating adequate internal consistency. Conclusion: The Indonesian version of the SSIS-RS instrument was said to be a valid and reliable tool for assessing students' social skills in physical education learning, so that it becomes a reference instrument when measuring affective learning abilities. The importance of social skills possessed by students because it is a predictor of academic and future success.